Gross Domestic Product or Gross National Happiness – Which is the Better Alternative for Economic Measurement? - Marikina, Maria (Research Papers, 2020)
This article analyze the problem related to measuring the national economy and choosing the appropriate macroeconomic indicator. The object of the analysis will be the measurement of the economy, subject matter is the nature and the inconsistencies of the gross domestic product (GDP) and Gross National Happiness (GNH). This challenge also relates to the thesis, namely: GDP remains the main macroeconomic indicator, and other alternatives, such as GNH, can`t replace it altogether, as they give rise to new problems and inability to accurately assess.
Keywords: Gross domestic product; Economic well-being; Gross national happiness; Economic measuring